2021
DOI: 10.1519/jsc.0000000000004057
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Squat Jump Force-Velocity and Load-Velocity Profiles

Abstract: The reliability of the squat jump force-velocity and loadvelocity profiles. J Strength Cond Res 36(11): 3000-3007, 2022-The purpose of this study was to investigate the between-session reliability of the squat jump force-velocity (FV) and load-velocity (LV) profiles. Eighteen subjects (age 5 28.1 6 4.8 years; height 5 1.7 6 9.7; body mass 5 74.7 6 12.8) who could back squat .1.5 times body mass participated in this study. Each subject completed a familiarization session, followed by 2 experimental sessions eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 32 publications
1
22
2
Order By: Relevance
“…In contrast, 3 recent studies have reported poor reliability of FvP profile outputs (notably v 0 and S Fv ) obtained during jumping using various methods, including computation-based and reference methods. [2][3][4] The interpretations and conclusions provided by the authors clearly challenge both the methods and the FvP concept relevance: "The squat jump Fv [ : : : ] profiles established with a force plate are not reliable. Therefore, these profiles are not recommended to be used to inform programming decisions," 4 and "Coaches and researchers should be aware of the poor reliability of the Fv variables obtained from vertical jumping," 2 or "Fv variables [ : : : ] seemed to present a low between-day reliability."…”
Section: Reliability Of Fvp Profile Variables: Experimental Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, 3 recent studies have reported poor reliability of FvP profile outputs (notably v 0 and S Fv ) obtained during jumping using various methods, including computation-based and reference methods. [2][3][4] The interpretations and conclusions provided by the authors clearly challenge both the methods and the FvP concept relevance: "The squat jump Fv [ : : : ] profiles established with a force plate are not reliable. Therefore, these profiles are not recommended to be used to inform programming decisions," 4 and "Coaches and researchers should be aware of the poor reliability of the Fv variables obtained from vertical jumping," 2 or "Fv variables [ : : : ] seemed to present a low between-day reliability."…”
Section: Reliability Of Fvp Profile Variables: Experimental Resultsmentioning
confidence: 99%
“…[2][3][4] The interpretations and conclusions provided by the authors clearly challenge both the methods and the FvP concept relevance: "The squat jump Fv [ : : : ] profiles established with a force plate are not reliable. Therefore, these profiles are not recommended to be used to inform programming decisions," 4 and "Coaches and researchers should be aware of the poor reliability of the Fv variables obtained from vertical jumping," 2 or "Fv variables [ : : : ] seemed to present a low between-day reliability." 3 Unfortunately, input measurement reliability and questionable testing procedures are largely overlooked as a potential cause of error in the "take-home" messages and conclusions.…”
Section: Reliability Of Fvp Profile Variables: Experimental Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may have affect results and agreements between methods in the calculation of the intercepts of the linear F-v relationship, F 0 (N•kg 21 ) and v 0 (m•s 21 ). Therefore, for a given body mass, 1 subject jumped against a higher relative load than the next subject, thereby potentially affecting the slope of the F-v relationship (30,52). The intercepts are extrapolated from the data points along the slope and are essentially estimates of theoretical maximal values, although frequently discussed as determinants of jump performance.…”
Section: Discussionmentioning
confidence: 99%